The trans-atlantic journey of Gumbé: where and why has it survived? - Jackson, Rachel (African Music : Journal of the International Library of African Music, 2012)
The word 'gumbe' is extremely difficult to define. Gumbé can refer to a specific drum, dance, rhythm or social context. For the purposes of my research I define gumbé as both a drum and a genre of dance music. Ultimately the drum and the genre are inherently linked: tracing the transatlantic journey of the gumbe drum illuminates varying conceptions of gumbé as a genre.